2021
DOI: 10.3390/ijms22084096
|View full text |Cite|
|
Sign up to set email alerts
|

Decursinol Angelate Arrest Melanoma Cell Proliferation by Initiating Cell Death and Tumor Shrinkage via Induction of Apoptosis

Abstract: Melanoma is known to aggressively metastasize and is one of the prominent causes of skin cancer mortality. This study was designed to assess the molecular mechanism of decursinol angelate (DA) against murine melanoma cell line (B16F10 cells). Treatment of DA resulted in growth inhibition and cell cycle arrest at G0/G1 (p < 0.001) phase, evaluated through immunoblotting. Moreover, autophagy-related proteins such as ATG-5 (p < 0.0001), ATG-7 (p < 0.0001), beclin-1 (p < 0.0001) and transition of LC3-I… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(10 citation statements)
references
References 58 publications
0
10
0
Order By: Relevance
“…Decursinol angelate exerted growth inhibitory effects against murine melanoma B16F10 cells and xenograft mice model by arresting cell cycle at G0/G1 via suppression and downregulation of cyclin D1 and cyclin‐dependent kinases such as CDK2, CDK4 and CDK5 and upregulation of p21 that is a CDK inhibitor. Besides, DA treatment caused inhibition of autophagosome formation (expression of ATG‐5, ATG‐7, beclin‐1, and conversion of LC3‐I to LC3‐II were markedly decreased) and induced apoptosis via Bcl2 downregulation, Bax upregulation, activation of caspases (caspase‐9, caspase‐3), the release of cytochrome C, and generation of ROS that ultimately caused oxidative burst in B16F10 cells (Chang et al, 2021).…”
Section: Angelica Gigasmentioning
confidence: 99%
“…Decursinol angelate exerted growth inhibitory effects against murine melanoma B16F10 cells and xenograft mice model by arresting cell cycle at G0/G1 via suppression and downregulation of cyclin D1 and cyclin‐dependent kinases such as CDK2, CDK4 and CDK5 and upregulation of p21 that is a CDK inhibitor. Besides, DA treatment caused inhibition of autophagosome formation (expression of ATG‐5, ATG‐7, beclin‐1, and conversion of LC3‐I to LC3‐II were markedly decreased) and induced apoptosis via Bcl2 downregulation, Bax upregulation, activation of caspases (caspase‐9, caspase‐3), the release of cytochrome C, and generation of ROS that ultimately caused oxidative burst in B16F10 cells (Chang et al, 2021).…”
Section: Angelica Gigasmentioning
confidence: 99%
“…Autophagy as a protective role to ameliorate ROS-induced apoptosis. Several studies have reported that various anticancer agents are employed to treat melanoma through ROS production and ROS-mediated apoptosis (77,78). Kalantuboside B, a natural bufadienolide derivative, has been demonstrated to enhance intracellular ROS levels, which induce apoptosis and autophagy; moreover, apoptosis was revealed to be potentiated by the autophagy inhibitors chloroquine and 3-methyladenine in A2058 melanoma cells and xenografts, suggesting that autophagy plays a protective role in melanoma (9).…”
Section: Role Of Ros-induced Autophagy In Melanoma Treatmentmentioning
confidence: 99%
“…A possible explanation is that the functional effects of ROS-induced autophagy on cancer cell death are dependent on the type of oxidative stress, as well as the quantity and location of the ROS produced ( 92 ). It should be noted that anticancer drug-induced ROS also inhibit cytoprotective autophagy to promote apoptosis, and that blocking autophagy fails to affect ROS generation ( 78 , 89 ), suggesting that ROS serve as messengers to modulate autophagy and thus determine the cell fate. In this context, further clarifying the role of anticancer drug-induced ROS and the resultant autophagy is essential for melanoma treatment.…”
Section: Role Of Ros-induced Autophagy In Melanoma Treatmentmentioning
confidence: 99%
“…Beclin-1 is a highly conserved autophagy regulator protein in eukaryotic cells, which is mainly responsible for inducing the nucleation of autophagosomes during autophagy. Overexpression of Beclin-1 enhances autophagy and reduces apoptosis ( Chang et al, 2021 ). It has been found that Beclin-1 relocates to MERCs and interacts with PINK1 to promote the formation of MERCs and autophagosome precursor in mitophagy and starvation-induced autophagy ( Gelmetti et al, 2017 ).…”
Section: Biological Functions Of Mercsmentioning
confidence: 99%